Analyzing the humorous communicative interactions during the wartimes in Aceh - Jarjani Usman; Fauzan Fauzan (Studies in English Language and Education, 2020)
Prolonged armed conflicts between the Government of Indonesia and the Free Aceh Movement/Gerakan Aceh Merdeka (GAM) happened from 1976 to 2005. The three-decade-vertical political conflicts have received worldwide attention in research, except its humorous sides. This study attempted to capture the types and styles of humor within the memories of Aceh society. To do so, this qualitative study used interviews and document analysis to interview 20 Acehnese people from five districts in Aceh province who experienced the vertical wars in Aceh and analyze written resources. The research found that there are many types and styles of humor that happened unintentionally as the result of the speakers’ mistranslating and miscode-mixing from Acehnese language to Indonesian language during unexpected interactions. Most of the humor occurring during the wars in Aceh fall into the incongruity theory, the verbal pun style, and the self-enhancing style. The findings of the study provide insights on the humorous side of the long wars through communicative interactions in Aceh that are useful to relieve tension when remembering the bitterness of the wars.